Plasma-Derived Polyreactive Secretory-Like IgA and IgM Opsonizing Salmonella enterica Typhimurium Reduces Invasion and Gut Tissue Inflammation through Agglutination - Bioley, Gilles; Monnerat, Justine; Lötscher, Marius; Vonarburg, Cédric; Zuercher, Adrian; Corthésy, Blaise (Frontiers in Immunology, 2017)
Due to the increasing emergence of antibiotic-resistant strains of enteropathogenic bacteria, development of alternative treatments to fight against gut infections is a major health issue. While vaccination requires that a proper combination of antigen, adjuvant and delivery route is defined to elicit protective immunity at mucosae, oral delivery of directly active antibody preparations, referred to as passive immunization, sounds like a valuable alternative. Along the gut, the strategy suffers however from the difficulty to obtain sufficient amounts of antibodies with the appropriate specificity and molecular structure for mucosal delivery. Physiologically, at the antibody level, the protection of gastrointestinal mucosal surfaces against enteropathogens is principally mediated by secretory IgA and secretory IgM. We previously demonstrated that purified human plasma-derived IgA and IgM can be associated with secretory component to generate biologically active secretory-like IgA/M (SCIgA/M) that can protect epithelial cells from infection by Shigella flexneri in vitro. In the present study, we aimed at evaluating the protective potential of these antibody preparations in vivo. We now establish that such polyreactive preparations bind efficiently to Salmonella enterica Typhimurium and triggers bacterial agglutination, as observed by laser scanning confocal microscopy. Upon delivery into a mouse ligated intestinal loop, SCIgA/M-mediated aggregates persist in the intestinal environment and limit the entry of bacteria into intestinal Peyer’s patches via immune exclusion. Moreover, oral administration to mice of immune complexes composed of S. Typhimurium and SCIgA/M reduces mucosal infection, systemic dissemination and local inflammation. Altogether, our data provide valuable clues for the future appraisal of passive oral administration of polyreactive plasma-derived SCIgA/M to combat infection by a variety of enteropathogens.